13 Edward I, ch. 6 (1285), in 1 Statutes of the Realm 97-98 (1800). - (:unkn) unknown (My University)
Required all males aged fifteen to sixty in certain income groups to have at least particular quantities of arms and armor.
Keywords: REQUIRED POSSESSION